A mesh‐type flexible tip catheter vs a contact force catheter for catheter ablation of atrial fibrillation: A prospective nonrandomized 1:1 matched study. (22nd April 2020) - Pak, Hui‐Nam; Park, Je‐Wook; Yang, Song‐Yi; Yu, Hee Tae; Uhm, Jae‐Sun; Joung, Boyoung; Lee, Moon‐Hyoung; Kim, Tae‐Hoon
Abstract: Introduction: Mesh‐type flexible tip (MFT) catheters allow clinicians to safely generate large radiofrequency lesions during catheter ablation of atrial fibrillation (AF), while contact force (CF) catheters provide better catheter‐tissue contact. We compared the clinical outcomes of catheter ablation of AF using MFT and CF catheters in a prospective, nonrandomized manner. Methods: We prospectively assigned 217 patients with AF (paroxysmal AF 73.5%; male 69.1%; 59.9 ± 10.7 years old) at a 1:1 ratio to ablation with MFT catheters (FlexAbility) or CF catheters (TactiCath). The primary endpoint was AF recurrence after a single procedure; the secondary endpoint was a response to antiarrhythmic drugs. Results: After a mean follow‐up of 22.3 ± 4.4 months, the clinical recurrence rate did not significantly differ between the two study groups (29.7% vs 30.2%; P  = .941) (log‐rank P  = .838). The recurrence rate for atrial tachycardias (30.3% vs 9.7%; P  = .035) and cardioversion rates (8.1% vs 1.9%; P  = .024) were higher in the MFT group than CF group. At the final follow‐up, sinus rhythm was maintained without antiarrhythmic drugs in 57.7% of the MFT group and 40.6% of the CF group ( P  = .010). No significant difference was found in the major complication rates between the two groups (0.9% vs 5.7%), although the ablation time was significantly longer in the MFT group (4192.1 ± 1080.2  vs 3583.8 ± 977.2 seconds; P  < .001). Conclusion: MFT and CF catheters had similar effectiveness in achieving AF rhythm control during catheter ablation, and there was no significant difference between the two catheters with regard to overall safety.